Preference Mapping of Thai Consumers for Commercial Green Tea with Roasted Brown Rice - Varaporn Vittayaporn; Penkwan Chompreeda; Vichai Haruthaithanasan; Hathairat Rimkeeree (Agriculture and Natural Resources, 2010)
The objectives of this study were to investigate: 1) sensory characteristics; 2) consumer acceptability of commercial green tea with roasted brown rice (genmaicha) available in Bangkok, Thailand; and 3) relationships between sensory attributes and consumer acceptance using preference mapping. The seven tea samples used in this study consisted of three brands of dried leaf tea (D) and four brands of infusion tea (I). The sensory descriptive analysis was conducted by eight trained panelists from the Kasetsart University Sensory and Consumer Research Unit (KUSCR). The panel identified 18 sensory attributes. The aroma and flavor intensities of green and seaweed attributes tended to be lower for infusion tea compared to dried leaf tea samples. However, the intensity of dry aroma tended to be higher for infusion tea than for the dried leaf tea samples. The results from principal component analysis (PCA) of descriptive data demonstrated that two principal components (PCs) could explain 87.31% of the variation. The samples were classified into three groups: 1) three brands of dry leaf tea; 2) three brands of infusion tea; and 3) one brand of infusion tea (I-B) with the latter containing stronger roast characteristics than the others. For the acceptability test, tea samples were also evaluated by 200 target consumers. The results of preference mapping identified attributes into 2 PCs, with PC1 being the aroma and flavor of green tea that could describe 66.80% of the variation and PC2 was the taste and aftertaste of tea that explained 17.10% of the variation. The higher tea and dry aromas, but the less intense roast aftertaste were the attributes that may drive consumers’ liking of green tea with roasted brown rice.